PERANCANGAN BRANDING DESTINASI PARIWISATA MELALUI SDM BERKUALITAS ALAS METAPA DESA PENINJOAN, KABUPATEN BANGLI - Agustina, Arik; Isha Aprinica, Ni Putu; Muliadiasa, I Ketut; Setiawan, Yoga (Berajah Journal, 2024)
Peninjoan Village has rich and unique natural tourism potential but has not been able to attract maximum tourist attention. The urgency of this research is to identify a tourism destination branding strategy design through the development of quality human resources (HR) in Penenjoan Village, Bangli Regency. The data collection techniques used were observation, interviews, documentation studies and questionnaires. This research focuses on designing a strong and effective tourism destination brand to increase the attractiveness of Peninjoan Village as a tourist destination.